2015
DOI: 10.3390/su70811032
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions of Tourism-Based Leisure Farms in Taiwan

Abstract: This research is the first attempt of a carbon emission investigation of tourism-based farms. A total of 36 cases were investigated. The result reveals that each tourist returns an average revenue of 28.6 USD and generates an average 10.9 kg-CO2eq per visit of carbon emissions. The average carbon emission density for each land area is 8.2 t/ha·year and is 245 kg/m²·year for each floor area. It is estimated that the overall carbon emissions reach 321,751 tons annually. The tourism-based farms were clustered int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, this does not mean that the tourism industry is a "zero emission" or "green" industry. A research from the World Tourism Organization reported that global CO 2 emissions from the tourism industry made up about 4.9 percent of the total global greenhouse gas emissions in 2005 [4], which were mainly originated from tourism transportation (accounting for about 75% of total tourism CO 2 emissions) [5,6], accommodation and catering (approximately 21%) [7,8], and tourist activities (approximately 4%) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, this does not mean that the tourism industry is a "zero emission" or "green" industry. A research from the World Tourism Organization reported that global CO 2 emissions from the tourism industry made up about 4.9 percent of the total global greenhouse gas emissions in 2005 [4], which were mainly originated from tourism transportation (accounting for about 75% of total tourism CO 2 emissions) [5,6], accommodation and catering (approximately 21%) [7,8], and tourist activities (approximately 4%) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Both the domestic and foreign literature estimate the energy consumption and carbon emissions of the tourism industry [23]. Therefore, in this study, the "bottom up" method is used to estimate the energy consumption and carbon emissions of the tourism industry in the YREZ.…”
Section: Study Methodsmentioning
confidence: 99%
“…From an overall perspective, the carbon emissions in the materialization stage are not high. However, considering the annual average carbon emissions [21,22], the carbon emissions in the materialization stage are much higher than those in the operational stage, making the study of this stage significant. Researchers have conducted studies on the calculation of carbon emissions in the materialization stage of buildings.…”
Section: Introductionmentioning
confidence: 99%